The physiological significance of β-actin mRNA localization in determining cell polarity and directional motility - Shestakova, Elena A. (The National Academy of Sciences, 2001)
β-actin mRNA is localized near the leading edge in several cell types, where actin polymerization is actively promoting forward protrusion. The localization of the β-actin mRNA near the leading edge is facilitated by a short sequence in the 3′ untranslated region, the “zip code.” Localization of the mRNA at this region is important physiologically. Treatment of chicken embryo fibroblasts with antisense oligonucleotides complementary to the localization sequence (zip code) in the 3′ untranslated region leads to delocalization of β-actin mRNA, alteration of cell phenotype, and a decrease in cell motility. To determine the components of this process responsible for the change in cell behavior after β-actin mRNA delocalization, the Dynamic Image Analysis System was used to quantify movement of cells in the presence of sense and antisense oligonucleotides to the zip code. It was found that net path length and average speed of antisense-treated cells were significantly lower than in sense-treated cells. Total path length and the velocity of protrusion of antisense-treated cells were not affected compared with those of control cells. These results suggest that a decrease in persistence of direction of movement and not in velocity results from treatment of cells with zip code-directed antisense oligonucleotides. To test this, direct analysis of directionality was performed on antisense-treated cells and showed a decrease in directionality (net path/total path) and persistence of movement. Less directional movement of antisense-treated cells correlated with a unpolarized and discontinuous distribution of free barbed ends of actin filaments and of β-actin protein. These results indicate that delocalization of β-actin mRNA results in delocalization of nucleation sites and β-actin protein from the leading edge followed by loss of cell polarity and directional movement.